Analysis of factors influencing intention to purchase halal Japanese food: The moderating role of religiosity - Afief El Ashfahany; Shafiyya Khansa Farrahvanaya; Muhamad Subhi Apriantoro; Suharjianto (Innovative Marketing, 2024)
The purpose of this study is to investigate the factors affecting the desire to purchase halal Japanese cuisine using the theory of planned behavior and religiosity as a moderator. The study employs the structural equation modeling partial least square (SEM PLS) method to analyze data obtained from questionnaires administered to 202 Muslim consumers at halal Japanese restaurants (Ramen Ya, Marugame Udon, and Sushi Tei). The findings demonstrate that attitudes (β = 0.228, p = 0.074), subjective norms (β = 0.198, p = 0.076), perceived behavioral control (β = 0.133, p = 0.035), and religiosity (β = 0.459, p = 0.000) significantly affect the intention to buy Japanese food labeled halal. In addition, halal awareness (β = 0.593, p = 0.000) and religiosity (β = 0.227, p = 0.039) also have a significant positive effect on attitude. However, the presence of religiosity does not significantly moderate the relationship between attitude, subjective norm, and perceived behavioral control towards purchase intention. Although religiosity does not act as a moderator, the outcomes of this analysis are expected to be useful for the Japanese halal cuisine sector, notably in countries with a majority Muslim population, to consider religiosity as an essential factor in increasing purchase intention. Acknowledgment The authors received financial support for the research, authorship, and publication of this article from Universitas Muhammadiyah Surakarta, Indonesia, under the Integration Research Grant Program (HIT).